Intensive Annual Forage Cultivation via Diversified Sowing Under a Mixed-Cropping System to Increase Production and Decrease Greenhouse Gas Emissions - Xiangyu Wei; Qin Feng; Jianqiang Deng; Haiying Hu; Qiaoli Ma; Jian Lan (Agriculture)
Intensive annual forage cultivation via diversified sowing can increase resource-use efficiency and meet the food requirements of the growing population. However, increasing cultivation time could increase energy demands and production costs with accompanying environmental hazards, such as greenhouse gas (GHG) emissions. A 2-year field experiment including three cropping systems (forage oat monoculture [O], forage oat–common vetch mixed-cropping [O/V], and common vetch monoculture [V]) and two sowing dates (spring and summer) was conducted to comprehensively assess productivity performance, energy utilization, and ecological efficiency under a cereal–legume mixed system over two sowing seasons in Northwestern China. The average system dry matter yield and economic benefit in the mixed system increased by 70.9% and 132.6%, respectively, compared to those of the monoculture system. The application of a mixed-cropping system increased energy efficiency and the ecoefficiency index (EEI) by 61.4% and 132.3%, respectively, with a decline in GHG emission intensity (GHGI) by 49.9%. Spring sowing increased average forage productivity and economic benefit by 9.3% and 18.6%, respectively, with a 23.0% decline in GHGI compared with that engendered by summer sowing. However, there was no correlation between the mixed-cropping system and single sowing date, and the average dry matter yield, economic benefit, and GHGI of the mixed-cropping system were 7.8 t ha−1, 1478.4 USD ha−1, and 0.3 kg CO2e kg−1, respectively. Furthermore, compared with the monoculture system, the combination of spring and summer seasons under the mixed-cropping system could increase the average annual system forage productivity, economic benefit, and EEI by 37.0%, 49.9%, and 53.1%, respectively, while reducing GHGI by 48.4%. This study demonstrates that the mixed forage oat and common vetch during spring and summer was the sustainable cropping system that achieved high system productivity, good economic returns, high energy utilization, and low environmental risk in Northwestern China.